2015
DOI: 10.1002/anie.201412070
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Based Design of Inhibitors of Protein–Protein Interactions: Mimicking Peptide Binding Epitopes

Abstract: Protein–protein interactions (PPIs) are involved at all levels of cellular organization, thus making the development of PPI inhibitors extremely valuable. The identification of selective inhibitors is challenging because of the shallow and extended nature of PPI interfaces. Inhibitors can be obtained by mimicking peptide binding epitopes in their bioactive conformation. For this purpose, several strategies have been evolved to enable a projection of side chain functionalities in analogy to peptide secondary st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
550
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 593 publications
(567 citation statements)
references
References 499 publications
(954 reference statements)
0
550
0
2
Order By: Relevance
“…150 In this study, a number of other fusicoccanes like Fusicoccin J aglycone (26) 150 and cotylenol (27) 150 (the aglycone of cotylenin) were tested ( Figure 15C). The respective crystal structures of the complexes of the different fusicoccanes with 14-3-3 and the TASK3 peptide revealed the structural basis for their "mode III" preference (26,22) or "mode III" specificity (23, Figure 16A). With a C12-dehydroxy fusicoccane like 22, concomitant binding of a "mode I" or "mode II" 14-3-3 partner like C-Raf and consequently its stabilization is possible ( Figure 16B).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…150 In this study, a number of other fusicoccanes like Fusicoccin J aglycone (26) 150 and cotylenol (27) 150 (the aglycone of cotylenin) were tested ( Figure 15C). The respective crystal structures of the complexes of the different fusicoccanes with 14-3-3 and the TASK3 peptide revealed the structural basis for their "mode III" preference (26,22) or "mode III" specificity (23, Figure 16A). With a C12-dehydroxy fusicoccane like 22, concomitant binding of a "mode I" or "mode II" 14-3-3 partner like C-Raf and consequently its stabilization is possible ( Figure 16B).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…), the SAH-BCL9 [42] and PRI-724 [43] compounds were developed as β-catenin inhibitors that fit into the shallow and extended interface created by PPI of β-catenin with BCL9 and CBP, respectively. Proteome-related technologies have also been applied in the challenging project to develop selective PPI inhibitors of other non-enzymatic cancer-related gene products, such as BCL2 family members and TP53 [44]. Drug development must utilize functional proteomics to prepare personalized therapeutic modalities for patients with cancerous as well as noncancerous diseases.…”
Section: Functional Proteomics For Personalized Medicinementioning
confidence: 99%
“…[19][20][21][22][23] A recent report used a structure-based approach involving rational defining of the protein interfaces of non-continuous and unstructured nature, to design peptides that bind IL-10R1 in vitro. 24 We proposed a way for designing IL-10 inhibiting peptides based on a helix segment of IL-10 within IL-10/IL-10R1 interaction region, and demonstrated that peptides with repeating pattern of hydrophobic and hydrophilic residues are able to inhibit IL-10 both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%